N-arachidonoyl-L-serine (AraS) Possesses Proneurogenic Properties in Vitro and in Vivo after Traumatic Brain Injury. Issue 8 (August 2013) - Cohen-Yeshurun, Ayelet; Willner, Dafna; Trembovler, Victoria; Alexandrovich, Alexander; Mechoulam, Raphael; Shohami, Esther; Leker, Ronen R
N -arachidonoyl-L-serine (AraS) is a novel neuroprotective endocannabinoid. We aimed to test the effects of exogenous AraS on neurogenesis after traumatic brain injury (TBI). The effects of AraS on neural progenitor cells (NPC) proliferation, survival, and differentiation were examined in vitro. Next, mice underwent TBI and were treated with AraS or vehicle. Lesion volumes and clinical outcome were evaluated and the effects on neurogenesis were tested using immunohistochemistry. Treatment with AraS led to a dose-dependent increase in neurosphere size without affecting cell survival. These effects were partially reversed by CB1, CB2, or TRPV1 antagonists. AraS significantly reduced the differentiation of NPC in vitro to astrocytes or neurons and led to a 2.5-fold increase in expression of the NPC marker nestin. Similar effects were observed in vivo in mice treated with AraS 7 days after TBI. These effects were accompanied by a reduction in lesion volume and an improvement in neurobehavioral function compared with controls. AraS increases proliferation of NPCs in vitro in cannabinoid-receptor-mediated mechanisms and maintains NPC in an undifferentiated state in vitro and in vivo. Moreover, although given at 7 days post injury, these effects are associated with significant neuroprotective effects leading to an improvement in neurobehavioral functions.